2000
DOI: 10.1177/0032885500080004003
|View full text |Cite
|
Sign up to set email alerts
|

Research on Sex in Prison During the Late 1980s and Early 1990s

Abstract: Research on sex in prison during the late 1980s and early 1990s was relatively rare in the published literature, despite important policy and practice considerations that provided a clear need for better understandings of such issues. The research that did appear during the period focused on one or two dominant themes and almost always focused on male inmates: consequences of the HIV/AIDS epidemic and efforts to document the incidence of sex among inmates. The marginality of such research is also seen in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 15 publications
(24 reference statements)
0
43
0
Order By: Relevance
“…Utilizing the theoretical framework established by Sykes (1958), one quality of prison life is "the deprivation of heterosexual relationships" (p. 70). A discussion of research on sexuality in prisons (see Hensley and Tewksbury 2002;Tewksbury and West 2000) can raise a number of legal, ethical, and policy-oriented questions. One author provides students with hypothetical scenarios for each deprivation; for sexuality, the scenarios can include conjugal visitation (including questions about whether same-sex visits should be permitted), condom distribution to inmates, prison rape prevention, and segregation of HIV-positive inmates, to name a few.…”
Section: Correctionsmentioning
confidence: 99%
“…Utilizing the theoretical framework established by Sykes (1958), one quality of prison life is "the deprivation of heterosexual relationships" (p. 70). A discussion of research on sexuality in prisons (see Hensley and Tewksbury 2002;Tewksbury and West 2000) can raise a number of legal, ethical, and policy-oriented questions. One author provides students with hypothetical scenarios for each deprivation; for sexuality, the scenarios can include conjugal visitation (including questions about whether same-sex visits should be permitted), condom distribution to inmates, prison rape prevention, and segregation of HIV-positive inmates, to name a few.…”
Section: Correctionsmentioning
confidence: 99%
“…Thus, it has been argued, there was no need for force or subjugation to occur (Hensley, 1999). Tewksbury and West (2000) posited that the sexuality of female offenders has been studied less than male offenders because women are generally considered less sexual than men are. Baro (1997) wrote that social science scholars have abandoned the study of sexual abuse of women in prison, perhaps because they believe that it is an isolated phenomenon and not suitable as a topic.…”
Section: University Of South Dakotamentioning
confidence: 99%
“…In addition, familial roles typical of kinship networks were not a significant aspect of daily life for the participants. Tewksbury and West (2000) reported that sexual behaviors readily identified as urgent and consequential from the standpoint of prison safety and security, such as sexual coercion, have been studied more often than other types of behaviors. When compared with the remaining categories of the proposed typology, the perceived inconsequential or nonproblematic nature of suppressed sexuality in prisons arguably has resulted in its failure to receive sustained research attention.…”
Section: Suppressed Sexualitymentioning
confidence: 99%
“…As the preceding observations suggest, to date, the study of sexuality in prison has been mostly dismissed, inadequately investigated, and/or negatively portrayed (Tewksbury & West, 2000). Consequently, the extant literature on convict sexuality is incomplete.…”
Section: Introductionmentioning
confidence: 99%